Person-centered care for dementia patients (back-end system development) - Low, Zachary Ee Young (Nanyang Technological University, 2022)
Dementia is a general term for the impaired ability to remember, think, or make decisions, interfering with everyday activities. With dementia affecting mostly older adults, the most common type of dementia is Alzheimer’s disease. It generally causes memory, attention, communication, reasoning, and judgement problems. It also affects their problem-solving skills. With these issues caused, families have been led to admitting older family members with dementia into nursing or care facilities to take care of dementia patients’ needs.